Contra: A programmable system for performance-aware routing - Hsu, Kuo-Feng; Beckett, Ryan; Chen, Ang; Rexford, Jennifer; Tammana, Praveen; Walker, David (NSDI, 2020)
We present Contra, a system for performance-aware routing that can adapt to traffic changes at hardware speeds. While point solutions exist for a fixed topology (eg, a Fattree) with a fixed routing policy (eg, use least utilized paths), Contra can operate seamlessly over any network topology and a wide variety of sophisticated routing policies. Users of Contra write network-wide policies that rank network paths given their current performance. A compiler then analyzes such policies in conjunction with the network topology and decomposes them into switch-local P4 programs, which collectively implement a new, specialized distance-vector protocol. This protocol generates compact probes that traverse the network, gathering path metrics to optimize for the user policy dynamically. Switches respond to changing network conditions by routing flowlets along the best policy-compliant paths. Our experiments show that Contra scales to large networks, and that in terms of flow completion times, it is competitive with hand-crafted systems that have been customized for specific topologies and policies.